Empirical research on coupling coordination degree of logistics industry and advantageous industries in Hu-Bao-Erdos urban agglomaration - Ying, Cui; Junhua, Liu; Zhimin, Tang; Yaru, Tain (Journal of Applied Science and Engineering A, 2021)
The advantageous industry in Hu-Bao-Erdos area is a composite industry including the energy chemical industry, metallurgical and building materials industry, agricultural and livestock products processing industry, equipment manufacturing industry, and strategic emerging industry. Based on panel data from 2011 to 2020, this paper measure and analyze the dynamic coupling synergy between the logistics industry system and the advantageous industries system the logistics industry system, and the five major advantageous industries subsystems. The results show that: in the past 10 years, the development level of the logistics industry is lower than that of the advantageous industry in Hu-Bao-Erdos, which restricts the development of the advantageous industries; the coupling synergy between logistics industry and the five dominant industries tends to be the same basically, and the logistics industry does not carry out deep coupling for a certain advantageous industry; the coupling synergy level between the logistics industry and the advantageous industry changes from being on the verge of imbalance to being mutually worn. It is in phase transition and still has a steady upward trend. In the future, Hu-Bao-Erdos Urban Agglomeration should vigorously develop the regional logistics industry, enhance its support and driving force for the development of regional advantageous industries, and further strengthen the coordination and cooperation between the logistics industry and the advantageous industries to achieve a higher level of coordination.